Determinants of decisions between clinician and patient to prescribe antimicrobials: A clinician’s perspective - Chalusa, Morris (Kamuzu University of Health Sciences, 2022)
Antimicrobial resistance is a great public health challenge which has been accelerated by the inappropriate use of antimicrobials. The inappropriate use of antimicrobials is associated with the increased risks of prolonged hospital stay, self-medication of self-limiting conditions and more admissions to hospitals. Some of the factors that increase antimicrobial resistance appear to be modifiable and are determine by clinician-patient communication. Increased antimicrobial resistance was the cause of severe infections in the year 2012 in Malawi. Out of a total of 100,000 recorded deaths, 70,200 (70.1%) were attributable to infectious diseases. A qualitative study was used to find out what factors determine the decision between clinician and patient to prescribe antimicrobials when not necessitated in Mulanje, Malawi, through the use of unstructured questionnaires, semi-structured interviews and focus group discussions. Clinicians’ knowledge of antimicrobial resistance as well as their communication skills was also sought. Interview and open ended survey responses were translated, transcribed and coded for themes. Participants pointed out that patient preferences, patient belief and clinician lack of education were among the factors that contribute to the decisions to prescribe antimicrobials. Most clinicians showed lack of knowledge on the definition of antibiotic and antimicrobial resistance. Inappropriate use of antimicrobials is facilitated by prescribing decisions made by clinicians who are greatly influenced by their patients. Improving antimicrobial prescription requires educational interventions for both clinicians and patients.